Differences in prescribing and dispensing at end-of-life between people who died at home before and during the Covid-19 pandemic in Scotland. - Savinc, Jan; Atherton, Iain (International Journal of Population Data Science, 2024)
Objectives To compare levels of palliative care need that were met through prescriptions and dispensing of medicines at end-of-life for people who died at home in Scotland during and prior to the Covid-19 pandemic. Approach Retrospective observational study of linked routinely collected data: death registrations in Scotland during 12-month pandemic period (starting 23rd March 2020) and pre-pandemic period (5 years prior), linked to inpatient hospital admissions and community prescribing & dispensing data. Prescribing/dispensing will be summarised for pandemic & pre-pandemic cohorts and palliative care needs estimated using death registrations and inpatient admissions. Results An estimated N=59,152 individuals died with palliative care needs during the first year of the pandemic, or approximately 11% more than in 2019/20. Community prescribing & dispensing will be compared between the pandemic and pre-pandemic periods as a proxy measure of primary care use and to investigate shortages. Anticipatory medication use will be compared to estimate quality of death at home for decedents. Conclusions Deaths at home increased by about a third during the first year of the pandemic in Scotland and continue at similar levels currently. Understanding the effect of the pandemic on prescriptions and dispensing at end-of-life will help explain the shift of deaths to home settings in addition to demographic and service contact changes early in the pandemic. Implications Studying the changes in end-of-life medication use will inform policy to better continue supporting people dying at home, especially where there are unmet needs or gaps between prescribed and dispensed medications.